The Position of Women in The Minangkabau Customary Inheritance System from The Mubadalah Perspective (A Study in Sidomukti Village, Gedung Aji Baru Subdistrict, Tulang Bawang Regency) - Muhammad Syauqi Al Mubarok; Habib Sulthon Asnawi; Ahmad Muslimin (CV. Bimbingan Belajar Assyfa, 2026)
This study examines the position of women in the Minangkabau customary high inheritance system and the Islamic legal values reflected in its practice in Sidomukti Village, Tulang Bawang, using the Mubadalah perspective. The research employs a qualitative method with a case study approach, collecting data through in-depth interviews, observation, and documentation. The findings reveal that normatively, women hold a strong position as the primary owners of high ancestral property within the matrilineal system. However, a gap exists between formal ownership and actual control, where men (mamak) dominate the management and decision-making processes. Inheritance practices reflect the values of justice (through deliberation), public interest (maslahah, based on needs), and responsibility (management by mamak), but the value of balance (tawazun) has not been fully achieved. The Mubadalah perspective recommends a relational reconstruction towards equal partnership, where women are not merely symbolic owners but active subjects. This study concludes that collective awareness is needed to achieve substantive and relational justice in Minangkabau customary inheritance practices.